ATP release and purinergic signaling in NLRP3 inflammasome activation - COUILLIN, Isabelle; GOMBAULT, Aurelie; Baron, Ludivine (Frontiers in Immunology, 2013)
The NLRP3 inflammasome is a protein complex involved in IL-1β and IL-18 processing that senses pathogen- and danger-associated molecular patterns (PAMPs and DAMPs). One step- or two step-models have been proposed to explain the tight regulation of IL-1β production during inflammation. Moreover, cellular stimulation triggers adenosine triphosphate (ATP) release and subsequent activation of purinergic receptors at the cell surface. Importantly some studies have reported roles for extracellular ATP, in NLRP3 inflammasome activation in response to PAMPs and DAMPs. In this mini review, we will discuss the link between active ATP release, purinergic signaling and NLRP3 inflammasome activation. We will focus on the role of autocrine or paracrine ATP export in particle-induced NLRP3 inflammasome activation and discuss how particle activators are competent to induce maturation and secretion of IL-1β through a process that involves, as a first event, extracellular release of endogenous ATP through hemichannel opening, and as a second event, signaling through purinergic receptors that trigger NLRP3 inflammasome activation. Finally, we will review the evidence for ATP as a key pro-inflammatory mediator released by dying cells. In particular we will discuss how cancer cells dying via autophagy trigger ATP-dependent NLRP3 inflammasome activation in the macrophages engulfing them, eliciting an immunogenic response against tumors.